Penentuan Pusat-Pusat Pertumbuhan dan Wilayah Pendukungnya Sebagai Upaya Pengembangan Wilayah Di Kabupaten Lombok Barat, Nusa Tenggara Barat - Baiq Ismiwati; Muhamad Sayuti (Fakultas Ekonomi Universitas Islam Al-Azhar, 2019)
This study’s title was “Determining Growth Poles and its Hinterland as an Effort of Region Developing in West Lombok Regency, West Nusa Tenggara”. The purpose was to know about which sub-district was the economy growth pole and its hinterland in West Nusa Tenggara Regency and to know about interaction beween sub-district that took role as the growth pole with its sub-district hinterland. The method used in this study was descriptive method with documentation technique and literature study as data collection technique. Data used was quantitative data with scalogram and gravitation analysis procedure. The result of the scalogram analysis showed that Narmada Sub-district was in the highest rank in the hierarchy level I, so it was suitable as growth pole for the Northern region of West Lombok Regency. Gerung Sub-district was in the hierarchy level II, so it was suitable as growth pole for Southern of West Lombok Regency. In the hierarchy level III were Lembar, Labuapi and Gunung Sari Sub-district. Meanwhile, the sub-district in hierarchy level IV were Sekotong, Kediri, Kuripan, lingsar, and Batu Layar Sub-district. Base on the gravitation analysis, Sub-district that had the most powerful interaction with Narmada Sub-district was Lingsar Sub-district, meanwhile the most powerful interaction with Gerung Sub-district was Kuripan Sub-district. Sub-district that had the most powerful interaction with the growth pole Sub-district was a hinterland that had an opportunity to developed so that it can increase its economic growth.